Association between taste receptor (TAS) genes and the perception of wine characteristics - Maura Carrai (Nature Portfolio, 2017)
Abstract Several studies have suggested a possible relationship between polymorphic variants of the taste receptors genes and the acceptance, liking and intake of food and beverages. In the last decade investigators have attempted to link the individual ability to taste 6-n-propylthiouracil (PROP) and the sensations, such as astringency and bitterness, elicited by wine or its components, but with contradictory results. We have used the genotype instead of the phenotype (responsiveness to PROP or other tastants), to test the possible relation between genetic variability and the perception of wine characteristic in 528 subjects from Italy and the Czech Republic. We observed several interesting associations, among which the association between several TAS2R38 gene single nucleotide polymorphisms (P = 0.002) and the TAS2R16-rs6466849 polymorphism with wine sourness P = 0.0003). These associations were consistent in both populations, even though the country of origin was an important factor in the two models, thus indicating therefore that genetics alongside cultural factors also play a significant role in the individual liking of wine.